Evaluation of the transversal actions of the New Deal: operational partnerships to promote employment for the Brussels residents? - Sabrine Cipriano; Catherine Fallon; Perrine Fastré; Jordan Halin (Brussels Studies, 2015)
In 2011, social partners and the Brussels government signed the New Deal, aimed at reinforcing the coherence of the Brussels employment policy through partnerships between the stakeholders concerned, both private and public. The evaluation of this public policy is a first in the Brussels-Capital Region. This article takes a reflective look at its results, obtained from case studies and focus groups. It provides an operational overview of the coordination mechanisms which have been implemented, according to the point of view of stakeholders involved in the New Deal: do these new methods of cooperation reveal the emergence of a new public governance in the Brussels Region? It shows that the transformations targeted by the New Deal in the area of governance between stakeholders in Brussels are characterised by the will for the transversality of public intervention, but in the end remain limited by the institutional division which it claims to transcend. The method of coordination, which is too informal and dependent on the stakeholders present – and even on people – and their means, would benefit from reinforcement, to guarantee the continuity of the approach and ensure that coordination is not reduced to a juxtaposition of stakeholders.